2018
DOI: 10.1038/s41598-017-18501-9
|View full text |Cite
|
Sign up to set email alerts
|

CLIQ-BID: A method to quantify bacteria-induced damage to eukaryotic cells by automated live-imaging of bright nuclei

Abstract: Pathogenic bacteria induce eukaryotic cell damage which range from discrete modifications of signalling pathways, to morphological alterations and even to cell death. Accurate quantitative detection of these events is necessary for studying host-pathogen interactions and for developing strategies to protect host organisms from bacterial infections. Investigation of morphological changes is cumbersome and not adapted to high-throughput and kinetics measurements. Here, we describe a simple and cost-effective met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Fluorescence microscopy using Hoechst nuclear stain [22] also revealed bacteria-induced damage to the human macrophages. Upon contact with pathogenic corynebacteria, DNA was successively condensing over time and nuclei appeared smaller and brighter as compared with cells, which had contact with non-pathogenic C. glutamicum (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence microscopy using Hoechst nuclear stain [22] also revealed bacteria-induced damage to the human macrophages. Upon contact with pathogenic corynebacteria, DNA was successively condensing over time and nuclei appeared smaller and brighter as compared with cells, which had contact with non-pathogenic C. glutamicum (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Network-based approaches were exploited to detect, reconstruct and study interactions among sub network modules ( 13 , 19 , 22 , 25 , 40 ); to assess functional correlation among multi-omics entities ( 12 , 14 , 20 , 55 , 61 , 62 ); to integrate and fuse networks to create comprehensive view of a disease ( 16 , 24 , 32 , 37 , 41 , 63 , 65 ). A few work leverage Bayesian methods ( 4 , 34 ) or Markov models ( 17 , 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest that the brain utilizes the glymphatic system ( 62 , 63 ) to clear fluid and metabolic waste, using a complex series of perivascular channels surrounding the brain's veins and arteries. It has been suggested that when the perivascular channels are compromised due to aging, disease, or trauma, the perivascular space becomes enlarged and consequently, visible on structural MRI ( 64 67 ). MRI-visible (enlarged) perivascular spaces (PVS) on T2 appear as small (<3 mm diameter), linear, hyperintensities following the course of the vasculature ( Figure 10 ).…”
Section: Methodsmentioning
confidence: 99%